Managing complexity in cross-cohort classrooms: strategies for effective implementation of real-life projects - Das, Syaamantak; Iyer, Sridhar (Frontiers in Education, 2025)
IntroductionReal-life project-based courses aim to enhance student learning by integrating authentic projects into the curriculum. However, the complexity of these projects, due to their VUCA (Volatile, Uncertain, Complex, and Ambiguous) nature, can pose significant challenges, especially for students new to the concepts and skills being taught. This study addresses the overarching question: “How can a systematic model be developed and implemented to effectively manage teaching and learning through developing a real-life project in a hybrid cross-cohort environment?”.MethodsThe study was conducted within an Instructional Systems Design (ISD) course in a hybrid cross-cohort class structure. A diverse class of 27 students with varying backgrounds participated in the course. Data were collected through surveys, interviews, and instructor observations. The implementation process involved multiple student cohorts, primary stakeholders of the project, subject matter experts, and instructors.ResultsThe study resulted in the development of the proposed 3 Square model to manage hybrid cross-cohort learning environments. Students engaged in developing a real-life project—a public awareness website for Persons with Disabilities (PwD) in a university environment. They navigated the complexities of coordinating within a cross-cohort classroom and developed critical skills such as autonomous decision-making and effective communication. Outcomes included efficient time management, achievement of project objectives, and tangible learning outcomes such as mastering ISD topics, using new tools, and working collaboratively in a group.DiscussionThe findings highlight the importance of leveraging diverse student knowledge and experience to manage challenges in cross-cohort classrooms for complex projects. Practical implications are discussed for instructional design and teaching strategies in diverse educational settings, emphasizing the need for systematic approaches to facilitate real-life problem-based learning tasks.ConclusionThis study provides a retrospective evolution of a systematic model for hybrid cross-cohort learning environments. It identifies teaching-learning challenges, determines appropriate instructional strategies, and evaluates the effectiveness of solutions in facilitating real-life project-based learning. The insights gained contribute to managing diverse educational settings and enhancing instructional design practices.